PENGARUH MODEL KOOPERATIF MAKE A MATCH TERHADAP HASIL BELAJAR IPAS SISWA KELAS V UPT SPF SD INPRES BONTOMANAI KOTA MAKASSAR - Khaerunnizah; Nasrah; Amri Amal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Student learning outcomes in the science and science subject for fifth grade students at SD Inpres Bontomanai, Makassar City are still relatively low, with an average score that has not yet reached the minimum completeness criteria (KKM). Based on observations, learning is dominated by the lecture method, so students are less active and less enthusiastic about learning. The aim of the research is to determine the effect of the Make A Match cooperative model on student learning outcomes in the Social Sciences subject for class V students. This type of research is Quasi-experimental with the total population in the experimental class, namely class V B and control, namely class V A, being 51 people. The research design uses a Non-Equivalent Control Group with the sample type, namely total sampling. By giving Pretest & Posttest. Based on the research results, there are differences in the two samples with the independent sample t test in the t test and sig. (2-tailed) of 0.008 < 0.05. This means that there is a significant difference between the posttest results of the experimental class and the control class. Referring to the decision, H0 is rejected and H1 is accepted (hypothesis is supported).